Desenvolvimento de um dispositivo de lubrificação automático para máquinas agrícolas - Peruzzo, Higor Artico (2025)
Industrial equipment is fundamental to the operation of various productive sectors, being responsible for automating, facilitating, and optimizing manufacturing, assembly, transportation, and quality control processes. All industrial equipment needs lubrication, which must be done periodically for greater durability and functionality. The lack of lubrication can lead to several problems, such as excessive wear of components, overheating, corrosion, bearing and other component failures, as well as reduced machine lifespan and loss of efficiency. With this in mind, manual lubricators emerge as a solution, allowing lubrication. However, they require the presence of an operator and are generally a tiring and dangerous task. Depending on the machine, the work demands a significant amount of time, resulting in increased production times, loss of lubricating material, and increased labor. This work aims to develop an automated lubrication device, with sensors that control the amount of material and the correct time foreseen by the manufacturer for the automatic lubrication of the equipment, with predefined stages of project planning, concept establishment, mechanical design, detailing and cost evaluation. The system consists of a tank, an electric pump, the electronic control assembly, crimped hoses, which guarantee the necessary robustness and elasticity, as well as improving ergonomics by reducing the effort required from the operator. As a result, this study presents the complete design of the automated lubrication device, as well as its financial feasibility analysis, demonstrating the technical and economic efficiency of the proposed solution.